Genetic advances in post-traumatic stress disorder - Guillén-Burgos, Hernan Felipe; Gutiérrez-Ruiz, Karol (Revista colombiana de psiquiatría (English ed.), 2018)
Post-traumatic stress disorder, or PTSD, is a condition that affects a subgroup of individuals that have suffered a previous traumatic event capable of generating changes at a psychological and behavioural level. These changes affect the personal, family, and social environment of those who suffer from this condition. Different genes have been identified as risk markers for development of this disorder. The population heterogeneity and individual differences (genetic and environmental) of each subject have made it difficult to identify valid markers in previous studies. For this reason, studies of Gene×Environment (G×E) have gathered importance in the last two decades, with the aim of identifying of the phenotypes of a particular disease. These studies have included genes such as SLC64A, FKBP5, and ADCYAP1R1, among others. Little is known about the interaction between the genes, pathways, and the molecular and neural circuitry that underlie PTSD. However their identification and association with stimuli and specific environments that stimulate the development of PTSD makes it focus of interest for identify genomic variations in this disorder. In turn, the epigenetic modifications that regulate the expression of genes involved in the hypothalamic–pituitary–adrenal (HPA) axis and the amygdala–hippocampal–medial prefrontal cortex circuits play a role in the identification of biomarkers and endophenotypes in PTSD. In this review, the advances in genetic and epigenetic that have occurred in the genomic era in PTSD are presented. El trastorno por estrés postraumático (TEPT) es una condición que afecta a un subgrupo de individuos que han sufrido un evento traumático con la capacidad de generar cambios psicológicos y conductuales. Estos cambios interfieren el entorno personal, familiar y social de los individuos. Diferentes genes se han identificado como marcadores de riesgo de esta enfermedad; sin embargo, la heterogeneidad poblacional y las diferencias individuales (genéticas y ambientales) han hecho difícil la identificación de marcadores genéticos válidos en los estudios realizados. Por tal motivo, han cobrado gran importancia en las ultimas dos décadas los estudios de relación entre gen y ambiente con la intención de identificar fenotipos propios de la enfermedad. Se han estudiado ampliamente genes como SLC64A, FKBP5 y ADCYAP1R1, entre otros. Poco se conoce de su interacción con las vías y los circuitos moleculares y neuronales que subyacen al TEPT, pero su identificación y asociación con estímulos y ambientes específicos condicionantes de la aparición del TEPT los hacen centro de interés para el estudio de identificación de variables genómicas en TEPT. A su vez, las modificaciones epigenéticas que regulan la expresión de genes vinculados en el eje hipotálamo-pituitario-adrenal y en el circuito amígdala-corteza prefrontal media-hipocampo son de gran interés para la identificación de biomarcadores y endofenotipos en TEPT. En esta revisión se podrá elucidar los avances en genética y epigenética que han acontecido en la comprensión genómica del TEPT.